An assessment of college teaching: case study - Kil, Yangsook; Kil, Myungsook (Opción, 2019)
This research evaluated six professors’ teaching practice to assess strengths and weaknesses, and suggested prescriptions for their teaching. Reflecting that the prevalent teaching method utilized by professors is direct instruction, a rubric consisting of 17 teaching behaviors for effective direct instruction was developed and used as a checklist. As a result, successfully performed behaviors were clear explanation of contents, utilizing instructional media for interest and comprehension, well organized contents in power point, and positive atmosphere. In conclusion, direct instruction oriented teaching and inefficient teaching behaviors of college professors call attention to ill-prepared professors in view of teaching